How would I check my answer on something like this? Usually, when I check my answer, it's a certain value I can just plug in, but here I'm not sure.
For some reason, it takes a while to understand that radicals are just numbers.
Here is how to check the answers to a quadratic
\(\displaystyle x^2 - 5x - 14 = 0 \implies \dfrac{(-5) \pm \sqrt{(-5)^2 - 4(1)(-14)}}{2 * 1} =\dfrac{5 \pm \sqrt{25 + 56}}{2} = \dfrac{5 \pm \sqrt{81}}{2} = \dfrac{5 + 9}{2}\ or\ \dfrac{5 - 9}{2} = 7/ or/ - 2.\)
You check by putting your answers back into the original equation.
\(\displaystyle 7^2 - 5 * 7 - 14 = 49 - 35 - 14 = 14 - 14 = 0.\) That answer checks.
\(\displaystyle (-2)^2 - 5(-2) - 14 = 4 + 10 - 14 = 14 - 14 = 0.\) That answer checks too.
Got that idea? You do the same thing if the answer contains a radical.
Now if you get an answer with a radical , it's actually easier because you only have to check one of the two answers.
\(\displaystyle x^2 + 3x + 1 = 0 \implies x = \dfrac{- 3 \pm \sqrt{3^2 - 4 * 1 * 1}}{2 * 1} = \dfrac{-3 \pm \sqrt{9 - 4}}{2} = \dfrac{- 3 \pm \sqrt{5}}{2}.\)
It turns out when we have symmetric answers like this, we need to check only one answer to confirm both answers.
\(\displaystyle \left(\dfrac{- 3 + \sqrt{5}}{2}\right)^2 + 3\left(\dfrac{- 3 + \sqrt{5}}{2}\right) + 1 = \dfrac{9 + 2(- 3) \sqrt{5} + 5}{4} + \dfrac{- 9 + 3\sqrt{5}}{2} + 1 = \dfrac{9 - 6\sqrt{5} + 5}{4} + \dfrac{- 18 + 6\sqrt{5}}{4} +\dfrac{4}{4} = \dfrac{9 + 5 + 4 - 18}{4} = 0.\)
That answer checks. Fussing with the radicals makes the arithmetic a bit harder so it is a blessing that you only have to check one of the two answers if they contain radicals.